Fireflies - Baharuddin, Nasir (Universiti Putra Malaysia Press, 2013)
This video tries to address a process of capturing light from fireflies by using videography technique in creating real scene of the object. The process being developed through the screening the fireflies images by filtering the artificial light to capture the light of the fireflies.